PRESPEKTIF HUKUM TERHADAP REGULASI MATA UANG KRIPTO DAN IMPLIKASI BAGI EKONOMI MASYRAKAT - Umi Paizah, Randini; Nadira, Putri; Muthi'ah Nurarfani, Hanin; Handayani, Sri (Cahaya Ilmu Bangsa, 2025)
The development of digital technology has led to the emergence of cryptocurrency as one of the key innovations in the global financial system. This study aims to analyze the legal perspective on cryptocurrency regulation and its implications for the community's economy. This research uses a method with a normative approach, based on current legislation and a comparative analysis of regulations in various countries. The findings show that cryptocurrency regulation in Indonesia is still limited and preventive, prohibiting its use as a means of payment but allowing its use as a tradable commodity. Nevertheless, cryptocurrency holds significant potential to promote financial inclusion and transactional efficiency, while also carrying high risks such as price volatility, fraud, and money laundering. Therefore, a comprehensive and adaptive regulatory framework is needed to provide legal certainty while supporting the sustainable development of the digital economy.